2002
DOI: 10.4049/jimmunol.168.10.5278
|View full text |Cite
|
Sign up to set email alerts
|

IFN-γ-Inducible Protein 10 (CXCL10) Contributes to Airway Hyperreactivity and Airway Inflammation in a Mouse Model of Asthma

Abstract: Allergic asthma is an inflammatory disease of the airways characterized by eosinophilic inflammation and airway hyper-reactivity. Cytokines and chemokines specific for Th2-type inflammation predominate in asthma and in animal models of this disease. The role of Th1-type inflammatory mediators in asthma remains controversial. IFN-γ-inducible protein 10 (IP-10; CXCL10) is an IFN-γ-inducible chemokine that preferentially attracts activated Th1 lymphocytes. IP-10 is up-regulated in the airways of asthmatics, but i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

13
139
0
1

Year Published

2003
2003
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 203 publications
(154 citation statements)
references
References 38 publications
13
139
0
1
Order By: Relevance
“…In addition, we demonstrated that ORMDL3 selectively regulates activation of the ER localized transcription factor ATF6α signaling branch, a pathway we have demonstrated in human lung epithelial cells is linked to SERCA-2b, which is implicated in airway remodeling in asthma (24). Finally, our studies demonstrate that ORMDL3 activates several metalloprotease, chemokine, and OAS-regulated genes, several of whom have also been implicated in the pathogenesis of asthma (7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24). Overall, these studies provide evidence for a mechanism to link an ER localized protein such as ORMDL3 to the pathogenesis of asthma.…”
Section: Discussionmentioning
confidence: 74%
See 3 more Smart Citations
“…In addition, we demonstrated that ORMDL3 selectively regulates activation of the ER localized transcription factor ATF6α signaling branch, a pathway we have demonstrated in human lung epithelial cells is linked to SERCA-2b, which is implicated in airway remodeling in asthma (24). Finally, our studies demonstrate that ORMDL3 activates several metalloprotease, chemokine, and OAS-regulated genes, several of whom have also been implicated in the pathogenesis of asthma (7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24). Overall, these studies provide evidence for a mechanism to link an ER localized protein such as ORMDL3 to the pathogenesis of asthma.…”
Section: Discussionmentioning
confidence: 74%
“…The importance of these ORMDL3-regulated genes to asthma is suggested from studies demonstrating increased expression of many of these mediators in the airways of human asthmatics (MMP-9, ADAM-8, CCL-20, CXCL-10, IL-8) (7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17), induction of these mediators by allergen inhalation in asthmatics (MMP-9, CCL-20, CXCL-10) (7,12,19), and inhibition of asthma outcomes in mice deficient in these genes (MMP-9, ADAM-8, CXCL-10) (8,9,11,20,21). In addition to the important role of CCL-20 on T-cell recruitment (12), and epithelial mucus production (14), in mouse models of asthma, there is a critical link between CCL-20 and TRAIL for Th2 cell activation and allergic airway inflammation (15).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, it is somewhat surprising that IFN-γ levels were increased in BAL fluid of mice exposed to both Hettstedt and Zerbst PM 2.5 , while airway hyperresponsiveness, OVA-specific IgE, and BAL eosinophils were increased in the Hettstedt PM 2.5 -exposed group. However, recent studies indicate that IFN-γ induces the production of the chemokine CXCL10, which promotes allergic inflammation and airway hyperresponsiveness in mice (Medoff et al 2002). Therefore, IFN-γ has dual roles, and both TNF-α and IFN-γ may contribute to allergic inflammation and airway hyperresponsiveness observed in mice exposed to Hettstedt PM 2.5 .…”
mentioning
confidence: 99%